2020
DOI: 10.3389/fcell.2020.587866
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Their Extracellular Vesicles: A Potential Game Changer for the COVID-19 Crisis

Abstract: Corona virus disease 2019 (COVID-19) is a global public health crisis. The high infectivity of the disease even from non-symptomatic infected patients, together with the lack of a definitive cure or preventive measures are all responsible for disease outbreak. The severity of COVID-19 seems to be mostly dependent on the patients’ own immune response. The over-activation of the immune system in an attempt to kill the virus, can cause a “cytokine storm” which in turn can induce acute respiratory distress syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…COVID-19 patients derived-EVs suggested that targeted drug delivery to treat pneumonia significantly reduced the cytokine storm and inflammation when compared to controls [ 32 , 37 , 38 ]. These EVs are capable of effectively inducing TH1 cellular response, giving more protection; more so than B -cell immunity [ [38] , [39] , [40] ]. The EV-induced TH1 response confers protection against airway challenge in mice models [ 37 , 41 ].…”
Section: Extracellular Vesicles and Vaccine Developmentmentioning
confidence: 99%
“…COVID-19 patients derived-EVs suggested that targeted drug delivery to treat pneumonia significantly reduced the cytokine storm and inflammation when compared to controls [ 32 , 37 , 38 ]. These EVs are capable of effectively inducing TH1 cellular response, giving more protection; more so than B -cell immunity [ [38] , [39] , [40] ]. The EV-induced TH1 response confers protection against airway challenge in mice models [ 37 , 41 ].…”
Section: Extracellular Vesicles and Vaccine Developmentmentioning
confidence: 99%
“…Mesenchymal stem/stromal cells (MSCs) were quickly viewed with significant promise to treat COVID-19 ( 11 ) and many studies were launched rapidly with several now completed and reported. MSCs are multipotent stem like cells which can be isolated from a number of adult and neonatal tissues including bone marrow, adipose, umbilical cord and placenta among the others ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The severity of the COVID-19 disease is mostly dependent on the patient responses. Over-activation of the immune system, developed in the attempt to kill the SARS-CAV-2 virus, can cause a "cytokine storm" which in turn can induce an acute respiratory distress syndrome (ARDS: [44,89]), a multi-organ damage, ultimately leading to death (miR-258, miR-266, Table 1). In COVID-19 patients, the immunomodulatory properties of MSCs ameliorate the cytokine storm by inhibiting or modulating the pathological events, especially those of severe cases [87][88][89].…”
Section: Covid-19 Diseasementioning
confidence: 99%